Social support, pay satisfaction, work ability, and intention to stay: a case of return to work program participants - Johanim Johari,; Fatimah Zailly Ahmad Ramli,; Harlida Abdul Wahab,; Muhammad Firdaus Bidin,; Roshaimi Mat Rosely, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main objective of this study is to examine the influence of social support and pay satisfaction on intention to stay among employees who have undergone return to work (RTW) program. Work ability is also assessed as the mediating variable to explain the indirect link between the independent and dependent variables. A survey was conducted among employees across various sectors in the Klang Valley. A total of 187 responses were gathered and data was analyzed using Statistical Package for Social Sciences (SPSS) and Partial Least Square (PLS) 2.0. Based on the statistical analyses, it was found that pay satisfaction was significantly related to work ability of RTW participants but social support did not pose any substantial impact on this outcome. Work ability was also reported to have exerted a significant impact on RTW participants’ intention to stay. Furthermore, the result indicated that work ability provided a significant mediating effect on the link between pay satisfaction and intention to stay. Drawing on the findings, discussions highlighted on the plausible reasons why pay satisfaction is crucial in enhancing work ability and in ensuring that RTW participants continue to retain their present employment. Finally, this study also provides important theoretical and practical ramifications for practitioners in developing measures to elevate the intention to stay among RTW participants.